PENERAPAN STRATEGI MATHEMATICAL INVESTIGATION UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VI SD NEGERI 024 TARAI BANGUN KECAMATAN TAMBANG KABUPATEN KAMPAR - Evi Yenti (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research was motivated by the low learning outcomes of MTK class VI students of SDN 024 Tarai Bangun KecamatanTambang Kabupaten Kampar. This study aims to improve student learning outcomes in mathematics learning throughmathematical investigation strategies in the sixth grade students of SDN 024 Tarai Bangun Kecamatan Tambang KabupatenKampar. The subjects of this study were all sixth grade students of SDN 024 Tarai Bangun Kecamatan Tambang KabupatenKampar, totaling 18 people, in 2017. The form of this research was classroom action research. This research instrumentconsists of performance instruments and data collection instruments in the form of observation sheets of teacher activitiesand student activities. Based on the results of the research and discussion, it can be concluded that the MathematicalInvestigation learning strategy can improve the mathematics learning outcomes of the sixth grade students of SDN 024 TaraiBangun Kecamatan Tambang Kabupaten Kampar in 2017. On the basic score, the results of learning were 7 people whoachieved KKM or 38, 89% with an average learning outcome of 63. In the first cycle of mathematics learning outcomesobtained by students is the number of students who achieve mastery in learning is 72.22%. The average student learningoutcomes classically in cycle I is 71 or 13 people who achieve KKM and categorized as incomplete. Whereas in the secondcycle there were 17 people who reached the KKM with a completeness percentage of 94.44%. The implementation of theaction in the second cycle is more smooth when compared to the implementation of the actions in the first cycle. It can beseen that there was an increase from the basic score to the first cycle as many as 6 people while from the first cycle to thesecond cycle there were 4 people who achieved the KKM completeness